Activation of Kv3.1 channels in neuronal spine-like structures may induce local potassium ion depletion - Wang, Lu-Yang (The National Academy of Sciences, 1998)
Spines are specialized neuronal membrane structures, often localized at sites where synaptic information is relayed from one cell to another in the central nervous system. By electron immunomicroscopy we have found that the mammalian Shaw family potassium channel Kv3.1 is localized on spine-like protrusions, adjacent to postsynaptic membranes of bushy cells in the cochlear nucleus. As direct characterization of the electrophysiological behavior of ion channels in such structures is difficult, we have used Kv3.1-transfected CHO cells to create artificial spine-like membrane compartments. Membrane patches were sucked into microelectrodes to form small, cell-attached vesicles with dimensions comparable to those of the neuronal structures. Currents mediated by the Kv3.1 channel in these vesicles undergo rapid and complete inactivation, in contrast to their noninactivating behavior in whole-cell recordings. This apparent inactivation is caused by the rapid depletion of K(+) from the vesicle and the slow refilling of K(+) into the vesicle compartment from the bulk cytoplasm. Our data provide evidence that compartmentalized ionic transients can be generated in spine-like membrane structures and support the view that the localization of ion channels in spine-like structures may influence responses to synaptic stimulation.